KONSEKUENSI HUKUM DAN SOSIAL PERCERAIAN DI LUAR PENGADILAN AGAMA DI INDONESIA - Irsan Harahap; Uswatun Hasanah (Yayasan Baitul Hikmah al-Zain, 2026)
Divorce constitutes a legal event that carries significant juridical and social implications for family life. In Indonesia, the practice of divorce conducted outside the Religious Court is still found within society, particularly among Muslim communities, despite the normative provisions stipulated in Law Number 1 of 1974 on Marriage, which explicitly mandate that divorce may only be effected before a court of law. This study aims to analyze the legal and social consequences of divorces carried out outside the Religious Court within the framework of the national legal system. Employing a normative legal research method with statutory and conceptual approaches, this study is supported by an extensive review of legislation, court decisions, and doctrines of Islamic family law. The findings indicate that divorce for Muslim couples is legally valid only when it is pronounced through a decision of the Religious Court. Nevertheless, in social practice, divorces conducted outside the Religious Court—either unilaterally or through oral agreements between the parties—remain prevalent. Such practices generate complex implications. From a juridical perspective, divorces conducted outside the court lack legal force, resulting in the marriage status remaining administratively valid, which in turn complicates the fulfillment of civil rights, including the division of marital property, inheritance rights, and the issuance of divorce certificates. From a social perspective, this condition has the potential to give rise to stigma, discrimination, and socio-economic vulnerability, particularly for women and children. Furthermore, from the standpoint of state administration, out-of-court divorces create obstacles in civil registration processes and weaken legal protection mechanisms for children. This article underscores the urgency of law enforcement and the enhancement of public awareness regarding legally valid divorce procedures in accordance with Indonesian law in order to ensure legal certainty, the protection of women’s and children’s rights, and orderly state administration.